An Indian Gaur (Bos gaurus) Gores in the Western Ghats-A case report - Freston Marc Sirur; Priya Dugani; Neeraja A. Nair; Sudiksha; Vrinda Lath (Trauma Case Reports)
The forests of the Western Ghats are home to the tallest bovine in the world, the Indian Bison. While attacks are few, they may result in life-threatening injury. We report the case of a 57-year-old agriculturist who got gored by an Indian Gaur resulting in penetrating chest and abdominal trauma resulting in injuries to multiple organs. A prompt Emergency department evaluation and surgical repair of his injuries enabled recovery, with some residual disability.